Pengaruh Pemberian Contract Relax StretchingTerhadap Tingkat Kelincahan Pemain UKM Bola Voli Putri UMS Tahun 2015 - Yunitasari, Rima, Agus Widodo, S.Fis.,Ftr., M.Fis, Wahyuni, S.Fis.,Ftr.,M.Kes (2015)
Background: Women volleyball players need physical and good skill, in the form of agility that supports the outstanding achievement. Agility is related to flexibility, therefore it is required exercises such as contract relaxes stretching, this method is very effective to increase the flexibility, if flexibility increase agility will also increase. Research: To know the influence of granting contract relaxes stretching on the level of UMS women volleyball player's agility. Research Methods: The kind of this research is quasi experiment, with the one group pretest-posttest design. The manner of the sample collection purposing uses the method of sampling namely samples to be taken randomly on with criterion inclusion and exclusion, sample in order to obtain as much as 10 sample. Statistical analysis uses wilcoxon signed rang test with the abnormally distributed data. A measuring instrument agility using illionis agility test and exercise performed 3 times a week for 4 weeks. Result: Statistical analysis is taken by the results of difference average pre test and post test of 21,13 second and 17,29 second and the increase of 3,84 second. The results show there a significant change to the value of p= .005 (<0.05). Conclusion: There is an influence of significantly increase in the agility after having the exercise of the contract relaxes stretching.